Preternatural - Jeffery, Celina (punctum books, 2011)
The preternatural, as explored by these artists, disturb the ontological boundaries of art, nature and metaphysics. They exist within the folds of classificatory thresholds: both beyond and between nature and supernature; human and animal; vegetable and mineral; living and dead. The confusion between animate and inanimate is a primary concern, a surreality which unites with the preternatural's love for reveling in the mysterious: bizarre fragments, unreadable words, objects of absurd scale, and distortions of the relativity of time and space flourish throughout this exhibition. Preternatural is the catalogue for a multi-site art exhibition (9 December 2011 through 17 February 2012, in Ottawa, Canada) that draws from the idea that art itself is a form of preternatural pursuit, in which the artists participating explore the bewildering condition of being in between the mundane and the marvelous in nature. It questions a world that understands itself as accessible, reachable, and 'knowable' and counters it with a consideration of this heterogenous proposition.